IMPLEMENTASI FUNGSI PENGAWASAN DPRD TERHADAP KEBIJAKAN KELUARGA DAN PERLINDUNGAN PEREMPUAN DI KABUPATEN KEPAHIANG DALAM PERSPEKTIF HUKUM KELUARGA - Herliansyah, Putrado (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This research seeks to provide an in-depth examination of how the Regional House of Representatives (DPRD) of Kepahiang Regency performs its supervisory function over family-related policies and women’s protection within the framework of Islamic Family Law. The study adopts a qualitative-descriptive approach with a juridical-sociological (socio-legal).. The findings indicate that the DPRD’s supervisory duties are executed through a combination of formal and informal mechanisms, including committee meetings, field inspections, and collaborative coordination with DP3A and the Regional Technical Implementation Unit (UPTD) for Women and Child Protection. Nonetheless, the study identifies several barriers that constrain its effectiveness, such as limited financial resources, weak institutional coordination, and insufficient gender literacy coupled with a lack of understanding of substantive Islamic legal principles among policymakers.